2014
DOI: 10.6026/97320630010263
|View full text |Cite
|
Sign up to set email alerts
|

Insilico docking study of compounds elucidated from helicteres isora fruits with ampkinase- insulin receptor

Abstract: Insulin receptor (IR) proteins were essential intracellular signaling peptides in the insulin action cascade. Insulin receptor substrate proteins (IRS-1and IRS-2) serve and regulate the insulin level in the normal insulin action. The broad role of IRS-1 and IRS-2 in cell growth and survival reveals a common regulatory pathway linking development, somatic growth, fertility, neuronal proliferation, and aging to the core mechanisms used by vertebrates for nutrient sensing. Such type of proteins were cyclic adenos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…123,124 Saponin-rich fractions also exhibit this activity in vitro and in vivo. 126,130 Molecular docking with insulin receptors was analyzed with compounds isolated from H. isora fruits, 183 and the results suggested that they may be useful for treating diabetes.…”
Section: Hepatoprotective Activitymentioning
confidence: 99%
“…123,124 Saponin-rich fractions also exhibit this activity in vitro and in vivo. 126,130 Molecular docking with insulin receptors was analyzed with compounds isolated from H. isora fruits, 183 and the results suggested that they may be useful for treating diabetes.…”
Section: Hepatoprotective Activitymentioning
confidence: 99%
“…The important docking parameters such as solvent accessibility, binding site prediction, hydrophobicity were analyzed in the receptor, the ligand and optimized for the docking as described elsewhere [22-28]. Active binding sites were predicted using the Cast P tool for studying the receptor protein ligand interactions [29-31]. Similarly, the active site binding sites of PL-peptide were predicted using the AcceleryTM and Cast P web tools.…”
Section: Resultsmentioning
confidence: 99%
“…Number of synthetic and natural coumarin derivatives have been reported to many studies such as antimicrobial [22,23], analgesic- anti-inflammatory (24) and anticancer activity [25-28]. A report has demonstrated that coumarin substituted benzothiazole suppresses the protein tyrosine kinase activity and the use of coumarin in cancer therapy is gaining attention [29]. Thus, we report the binding features of coumarin derivatives with CAIX in the context of cancer (Figure 1).…”
Section: Introductionmentioning
confidence: 99%